Sirenomelia: a case report with literature review - Sahu, Latika; Singh, Sunita; Gandhi, Gauri; Agarwal, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
We are presenting a case of Sirenomelia (Mermaid Syndrome), which is an extreme example of the caudal regression syndrome. It invariably presents with lower limb fusion, sacral and pelvic bony anomalies, absent external genitalia, imperforate anus, and renal agenesis or dysgenesis. There are approximately 300 cases reported in the literature, 15% of which are associated with twinning, most often monozygotic. The syndrome of caudal regression is thought to be the result of injury to the caudal mesoderm early in gestation. The case encountered was a stillborn baby.